EFEKTIVITAS PROGRAM PEMBINAAN TAHAP AKHIR UNTUK REINTEGRASI SOSIAL NARAPIDANA WANITA DI LAPAS WANITA DI KUPANG - Samara, Finsensius; De Araujo, Rojalia Rica; Erickdianto Sales, Christian; Wage, Guido Tobhi; Pramana, Hanif Al Faiq; Perdinandus Goa, Christian (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study aims to analyze the effectiveness of the final-stage rehabilitation program for female inmates at the Class IIB Women’s Correctional Facility (Lapas Wanita Kelas IIB) in Kupang in the context of social reintegration. The final-stage rehabilitation plays a crucial role in preparing inmates to adapt and contribute positively to society after release. This research employs an empirical approach, utilizing primary data through interviews and secondary data from related sources. The findings indicate that the rehabilitation program includes psychological counseling, vocational training, spiritual strengthening, and family support. However, its implementation faces various challenges, such as limited resources, inadequate post-release support, and persistent social stigma. The evaluation of inmate progress during the final stage highlights the importance of monitoring and ongoing assistance to prevent recidivism. Therefore, this study recommends strengthening reintegration programs based on the specific needs of female inmates, increasing resource allocation, and conducting public awareness campaigns to promote social acceptance of former inmates. The success of these programs is expected to help female inmates return to society better prepared and more productive.